Voting and Social Media-Based Political Participation - Sascha Göbel (Journal of Quantitative Description: Digital Media)
Does online political involvement reinforce or compensate participatory deficiencies at the polls? Extant survey evidence portrays online participation as a weapon of the strong, wielded by a highly politically involved, white, and affluent subset of the American electorate. Surveys face systematic sampling and measurement errors in the domain of political participation, however. In this study, I revisit this question using individual voter registration records that I integrate with observed Twitter activity. Based on a large sample that reflects Florida's voting-eligible population, I find that political involvement on Twitter is prevalent across the electorate and extends to those most likely to abstain from voting. Moreover, race and income, which are salient dividing lines in voting, do not structure social media-based political participation, and common turnout patterns for age and party subgroups are reversed, though especially among more engaged voters. These results offer a novel perspective on reinforcement theory and social media's compensatory potential for more inclusive representation. I discuss implications for political representation and future research examining political involvement.